Analisis Faktor Yang Mempengaruhi Kinerja Usaha Mikro Kecil dan Menengah (UMKM) Kota Tebing Tinggi - Mirwansyah Putra Ritonga; Komala Dewi (Jurnal Ekonomi dan Pembangunan Indonesia, 2023)
The development of Small and Medium Enterprises (SMEs) is one of the government's priorities, especially in Tebing Tinggi City. Known as an industrial city, it becomes an opportunity for the development of SMEs, which are the majority of the workers. The development of SMEs, especially "Culinary Clusters" that have high added value to economic growth, needs to be given greater attention to developed. The purpose of this study is to analyze the factors that influence the business performance of SMEs in Batam City. The method used to determine the relationship between these factors uses partial least square- structural equation modeling (PLS-SEM) with SmartPLS 3.0 software. The results of data processing show that internal and external factors influence the performance of SMEs. External factors consist of government policies, socio-economic conditions, and culture, the role of related institutions has a significant influence on the condition of internal factors consisting of aspects of human resources, finance, technical production, and marketing. External and internal factors have a positive and significant influence on the performance of SMEs.